1982
DOI: 10.1136/bmj.284.6326.1368
|View full text |Cite
|
Sign up to set email alerts
|

Side effects of benoxaprofen.

Abstract: Our results suggest that in the elderly a dose of 600 mg daily is associated with an unacceptable incidence of gastric side effects. It is not clear why elderly patients with osteoarthritis were more prone to gastric side effects than patients with rheumatoid arthritis. Tyson and Glynne reported that in patients over 60 with osteoarthritis benoxaprofen caused more gastric side effects than did ibuprofen, whereas in patients under 60 the reverse was true.4 Compared with other non-steroidal anti-inflammatory age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0
1

Year Published

1982
1982
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(14 citation statements)
references
References 1 publication
0
13
0
1
Order By: Relevance
“…1 ), également commercialisé en Suisse depuis peu (Coxigon®; Ely Lilly, Bâ le). Très tôt [1,14], ce médicament a été re connu responsable de réactions de photo sensibilisation avec photoonycholyse chez une proportion variable des patients traités, allant jusqu'à près de 50% [4], Il semble ac tuellement bien établi qu'il s'agit d'une réac tion de photosensibilisation de type photo toxique, comme l'ont montré les travaux ré cents de plusieurs auteurs [2,3,5,9], Fergu son et al [2] ont observé une réaction pho totoxique, lors de phototests, chez tous les patients traités au benoxaprofène. La nature de la photosensibilisation au carprofêne semble différente.…”
Section: Discussionunclassified
“…1 ), également commercialisé en Suisse depuis peu (Coxigon®; Ely Lilly, Bâ le). Très tôt [1,14], ce médicament a été re connu responsable de réactions de photo sensibilisation avec photoonycholyse chez une proportion variable des patients traités, allant jusqu'à près de 50% [4], Il semble ac tuellement bien établi qu'il s'agit d'une réac tion de photosensibilisation de type photo toxique, comme l'ont montré les travaux ré cents de plusieurs auteurs [2,3,5,9], Fergu son et al [2] ont observé une réaction pho totoxique, lors de phototests, chez tous les patients traités au benoxaprofène. La nature de la photosensibilisation au carprofêne semble différente.…”
Section: Discussionunclassified
“…Similarly, Hindson et al [10] found that wavelengths of 310-330 nm were most effective in producing photosensitisation and pointed out that these wavelengths corresponded to the absorption spectrum of benoxaprofen.…”
Section: Discussionmentioning
confidence: 94%
“…Their study also showed that Caucasian subjects were most photosensitive, whereas subjects with dark skins and those using broad spectrum sunscreens were more protected. The wavelengths (305-460 nm) selected in the present study were within the range previously shown to induce photosensitivity in rheumatoid arthritis patients and healthy volunteers [10,12]. In addition, the subjects included in the current double-blind study were not dark-skinned and had not been using sunscreens, hence they were not likely to be protected from any possible effects of radiation.…”
Section: Discussionmentioning
confidence: 95%
“…Table 5 shows that all nine were from doctors who had hospital appointments, as determined from the addresses given on the papers and from the Medical Directory of the year in which the papers were published. Further evidence of the importance of hospital clinicians derives from the recent reports concerning the adverse reactions induced by Opren (Goudie et al, 1982;Halsey & Cardoe, 1982;Hindson et al, 1982;Taggart & Alerdice, 1982). Again all were from hospital clinicians, some from the speciality in which the drug would be prescribed (rheumatology) and others from specialities which would be involved in treating the adverse reaction (dermatology, pathology and histopathology).…”
Section: Discussionmentioning
confidence: 97%